Geographic Differentials in Mortality of Children in Mozambique: Their Implications for Achievement of Millennium Development Goal 4 - Macassa, Gloria; Ghilagaber, Gebrenegus; Charsmar, Harry; Walander, Anders; Sundin, Örjan; Soares, Joaquim (Journal of Health, Population and Nutrition, 2012)
In the light of Mozambiques progress towards the achievement of Millennium Development Goal 4 of reducing mortality of children aged less than five years (under-five mortality) by two-thirds within 2015, this study investigated the relationship between the province of mothers residence and under-five mortality in Mozambique, using data from the 2003 Mozambican Demographic and Health Survey. The analyses included 10,326 children born within 10 years before the survey. Results of univariate and multivariate analyses showed a significant association between under-five mortality and province (region) of mothers residence. Children of mothers living in the North provinces (Niassa, Cabo Delgado, and Nampula) and the Central provinces (Zambezia, Sofala, Manica, and Tete) had higher risks of mortality than children whose mothers lived in the South provinces, especially Maputo province and Maputo city. However, controlling for the demographic, socioeconomic and environmental variables, the significance found between the place of mothers residence and under-five mortality reduced slightly. This suggests that other variables (income distribution and trade, density of population, distribution of the basic infrastructure, including healthcare services, climatic and ecologic factors), which were not included in the study, may have confounding effects. This study supports the thought that interventions aimed at reducing under-five mortality should be tailored to take into account the subnational/regional variation in economic development. However, research is warranted to further investigate the potential determinants behind the observed differences in under-five mortality. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12297 J HEALTH POPUL NUTR 2012 Sep;30(3):331-345